2020
DOI: 10.3390/cancers12061623
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Allele Expression and Clinical Outcome in De Novo Metastatic Prostate Cancer

Abstract: The prognostic value of human leukocyte antigen (HLA) class I molecules in prostate cancer (PCa) remains unclear. Herein, we investigated the prognostic relevance of the most frequently expressed HLA-A alleles in Greece (A*02:01 and HLA-A*24:02) in de novo metastatic hormone-sensitive PCa (mPCa), which is a rare and aggressive disease characterized by a rapid progression to castration-resistance (CR) and poor overall survival (OS), contributing to almost 50% of PCa-related deaths. We identified 56 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…The resulting repertoire is for example defined by foreign antigens from encountered viruses. In a small European cohort with de novo metastatic prostate cancer ( n = 56), HLA‐A*02:01 and HLA‐A*24:02 have been suggested to have prognostic implications [ 4 ], but beyond that, little is known about the role of HLA‐type and antiviral immunity in prostate cancer. Human cytomegalovirus (CMV), a common herpes virus, is a master modulator of the immune system [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting repertoire is for example defined by foreign antigens from encountered viruses. In a small European cohort with de novo metastatic prostate cancer ( n = 56), HLA‐A*02:01 and HLA‐A*24:02 have been suggested to have prognostic implications [ 4 ], but beyond that, little is known about the role of HLA‐type and antiviral immunity in prostate cancer. Human cytomegalovirus (CMV), a common herpes virus, is a master modulator of the immune system [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to HLA-B44 generally, specific HLA-B alleles that bring about radical glutamic acid substitutions in the anchor position of B44 were associated with a poor prognosis and better clinical outcomes with ICIs in NSCLC (11). Specific HLA-A alleles (A*02:01 and A*24:02) were also associated with the prognosis of metastatic hormone-sensitive prostate cancer (8). Studies on the implications of the HLA genotype in the immunotherapy response in other solid tumor types are also increasing (12,39).…”
Section: Ngs Typically Generates Short Read Lengths (Betweenmentioning
confidence: 92%
“…Alterations in the human leukocyte antigen (HLA) are implicated in tumor invasion and development via the promotion of T lymphocyte-mediated immune escape mechanisms (6). Recent research has shown that specific alterations in HLA class I loci are associated with the clinical outcomes of ICIs (7)(8)(9)(10)(11)(12), which increases the importance of accurate high-resolution HLA genotyping in immunooncology applications. The HLA gene complex encodes the major histocompatibility complex (MHC), which plays a major role in adaptive immunity by presenting pathogenderived peptides to T lymphocytes (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Antigen presenting MHCI molecules are highly polymorphic, especially at their peptide binding grooves, and therefore each allele can bind and present a restricted set of antigenic epitopes. As result/Consequently, individuals homozygous in at least one MHCI locus may present a smaller, less diverse repertoire of tumor antigens to CD8+ T cells and thus may be less likely to present potent epitopes that induce highly effective antitumor responses that can be enhanced by ICI therapy [ 135 , 136 ]. Given that only a small percentage of presented tumor antigens in cancer patients are immunogenic, it seems that even small differences in MHCI molecules can significantly affect the adaptive responses and the efficacy of immunotherapy.…”
Section: Mhci Expression In Cancersmentioning
confidence: 99%